Satisfaction With Clinician-Led Germline Genetic Counseling in Patients With Prostate Cancer. Issue 5 (5th November 2022) - Abusamra, Sophia M.; Solorzano, Marissa A.; Luke, Mallory; Quarles, Jake; Jacobs, Michelle F.; Das, Sanjay; Kasputis, Amy; Okoth, Linda A.; Patel, Milan; Seymore, Mariana; Caram, Megan E. V.; Dunn, Rodney L.; et al.
Abstract : Purpose: Indications for germline testing in prostate cancer patients have expanded substantially over the past decade. With a near-universal shortage of genetic counselors and increasing demand, increased access to genetic counseling is crucial. We sought to prospectively implement and assess a clinician-led approach to genetic counseling and testing. Materials and Methods: Patients with metastatic or localized prostate cancer meeting National Comprehensive Cancer Network® criteria for consideration of genetic testing were offered pre-test genetic counseling by their urologist or medical oncologist as part of their routine clinical care and concurrently approached for enrollment in the Germline Genetics in Prostate Cancer Study. Consented patients filled out a post-counseling survey using validated instruments to assess the quality of counseling. For patients who elected to undergo genetic testing, an additional validated questionnaire was completed following disclosure of results. The primary outcome was the proportion of patients undergoing testing, with a target >60% of patients. The secondary outcome was overall satisfaction with counseling, with a target >85% of patients. Results: A total of 275 patients enrolled, and 203 patients elected to undergo genetic testing. Post-counseling surveys were obtained from 265 patients, and post-genetic testing surveys were obtained from 132 patients. Patient satisfaction was high, with 98% of patients reporting being satisfied with the overall quality of pre-test counseling, and 74% of patients elected to undergo genetic testing. Conclusions: These results support the effectiveness of clinician-led genetic counseling in prostate cancer. With clinician training, this approach can be utilized to expand access to appropriate germline genetic testing.